2004
DOI: 10.1515/cclm.2004.027
|View full text |Cite
|
Sign up to set email alerts
|

Determination of urinary glyoxal and methylglyoxal by high-performance liquid chromatography

Abstract: Carbonyl stress compounds such as glyoxal and methylglyoxal have been recently attracting much attention because of their possible clinical significance in chronic and age-related diseases. A high-performance liquid chromatographic procedure has been developed for the simultaneous quantitation of glyoxal and methylglyoxal in human urine. The assay is based on the reaction of these compounds with 1,2-diamino-4,5-dimethoxybenzene to form fluorescent adducts, which are separated by reversed-phase high-performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Various reactive carbonyl compounds with low molecular weight have been proposed to play an important role in pathogenesis of many chronic and age related diseases as carbonyl stress [1,2]. Chronic hyperglycemia leading to tissue damage is the primary etiological factor in the pathogenesis of diabetic macrovascular disease and may contribute to macrovascular complications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Various reactive carbonyl compounds with low molecular weight have been proposed to play an important role in pathogenesis of many chronic and age related diseases as carbonyl stress [1,2]. Chronic hyperglycemia leading to tissue damage is the primary etiological factor in the pathogenesis of diabetic macrovascular disease and may contribute to macrovascular complications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Most IS used in the published methods are structurally related to MG such as 2,3-butanedione [26,29,33], 2,3-pentanedione [34], 3,4-hexanedione [35], or 2,3-hexanedione [36,37]. These IS can be added to the sample as a nonderivatized compound or as a compound previously derivatized with corresponding DA.…”
Section: Deproteinizationmentioning
confidence: 99%
“…Therefore, the incubations had to be performed in the dark and even in the atmosphere of nitrogen. It has been shown that some com-pounds that stabilize diamino derivatives (such as b-mercaptoethanol [40]) significantly decrease MG level [26], and that even the osmolality of incubation mixtures has the same effect on the derivatization process [34].…”
Section: Derivatizationmentioning
confidence: 99%
See 2 more Smart Citations